1986
DOI: 10.1007/bf00430436
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the nifLA operon of Klebsiella oxytoca NG13 and characterization of the gene products

Abstract: The complete nucleotide sequence of the regulatory operon nifLA of a nitrogen fixer Klebsiella oxytoca NG13 was determined, and the transcriptional start point was assigned by S1 mapping. The nifL protein (a repressor) was coded by an open reading frame of 1,485 bases, corresponding to a protein of 495 amino acids with a calculated molecular weight of 55,242. The open reading frame (1,572 bases) of the nifA protein (an activator), corresponding to a molecular weight of 58,649, was confirmed by in vitro transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…The UAS contains the conserved sequence TGT-N,o-ACA, While all Gram-negative diazotrophs examined contain nifA. a nifL-\ike gene has been identified only in species of Kiebsielia and Azotobacter (Kennedy, 1977;Kim et al. 1986;Drummond and Wootton.…”
Section: Introductionmentioning
confidence: 99%
“…The UAS contains the conserved sequence TGT-N,o-ACA, While all Gram-negative diazotrophs examined contain nifA. a nifL-\ike gene has been identified only in species of Kiebsielia and Azotobacter (Kennedy, 1977;Kim et al. 1986;Drummond and Wootton.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of nzjL (Kim et al, 1986;Drummond & Wootton, 1987) revealed a -Cys-X-XCys-region that is homologous with redox-sensitive sites in disulphide reductases such as thioredoxin, and with metal-binding sites in redox centres of rubredoxins and cupredoxins. Drummond & Wootton (1987) also found a similarity between the amino acid sequences flanking the Cys-containing site and regions of cytochrome c in which the two cysteines are involved in covalent binding of haem; the amino acids responsible for the 5th and 6th ligands to the iron of the haem in cytochrome c (histidine and methionine) are, however, missing.…”
Section: Introductionmentioning
confidence: 99%
“…The SalIdigested genomic DNA of A. /ipoferum FS 2 ) was analyzed by Southern hybridization with a 32P-labeled 850-bp KpnI-PvuII fragment of pNOA 1 4 ) containing the central region of the K. oxytoca NG 13 nifA gene. Hybridizations were done by the standard methods 8 ) with a modification; washing temperature was altered to 50°e.…”
Section: Methodsmentioning
confidence: 99%
“…pTVAI and pTVKI were constructed as follows: Ncol sites were introduced at the initiation co dons of the cloned A. /ipoferum FS n[fA gene and the K. oxytoca nifA gene 4 ) by site-directed mutagenesis with a change of the second encoded amino acid; from Pro to Ala in the A. /ipoferwn nifA gene and from Ile to Val in the K. oxytoca nifA gene.…”
Section: Methodsmentioning
confidence: 99%